PILKADA DAN MASA DEPAN PENGUATAN DEMOKRASI DI DAERAH - Fatkhurohman, Fatkhurohman (Jurnal Konstitusi, 2010)
It should be admitted that in formal juridical point of view, the realization of practices of democracy at the local level cannot be separated from the implementation of the election of local heads. Since its implementation is still characterized by destruction of democracy values, the situation will influence the future democracy at local level. Therefore, it is necessary to take real actions to place the meaning of democracy in its proper tract in order to realize the development in local areas  based on democracy.